Junior dancers` training progress control using blood lactate tests - Kadyrov, R. M.; Rodichkin, A. P. (Theory and Practice of Physical Culture, 2018)
The dancesport community presently gives a high priority to the initiatives to improve the 8-12 year-old dancers` training process efficiency to meet the modern competitive requirements. The study data and analyses demonstrate that the blood lactate variation data may be applied to trace the sub-maximal-intensity threshold being reached by dancers. The study included blood lactate tests in the competitive process to provide sound grounds for the educational experiment. The training process under the experiment included special physical practices 2-3 times a week to model competitive semifinal and final performances with the performance intensity rated at 70% of the actual competitive one. According to the educational experiment, these practices facilitate adaptation processes, optimize anaerobic glycolysis and facilitate professional progress as verified by the statistically significant reduction of the time necessary for promotion to the next mastery class. It is also important that the Experimental Group functionality rates were found significantly higher than the Reference Group ones as verified by the Ruffier performance test.